WORD OF MOUTH AND REFERENCE GROUPS ON HNI HERBAL PRODUCTS IN SURAKARTA - Ida Aryati Dyah; Dessyani Dessyani; Anna Probowati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to determine and prove both simultaneous and partial influence of HNI herbal product purchase decisions in terms of trust, word of mouth and reference groups. This study uses quantitative descriptive methods. The population of all consumers of HNI herbal products in Surakarta with a sample of 100 respondents. Sampling technique using random sampling. Data collection using questionnaires. Data analysis techniques used multiple linear regression analysis, F and R2 Test.The results showed that, based on the F test of product quality, word of mouth and reference groups simultaneously and significantly affect the decision to purchase herbal products HNI in Surakarta. These results prove that the better the trust, word of mouth and Reference Group then the purchase decision at halal mart Surakarta will increase significantly. Keywords: purchase decision, trust, word of mouth, group reference.